Physical activity, sedentary behavior, and long-term cardiovascular risk in young people： A review and discussion of methodology in prospective studies - Tarp, Jakob; Brønd, Jan Christian; Andersen, Lars Bo; Møller, Niels Christian; Froberg, Karsten; Grøntved, Anders (Journal of sport and health science, 2016)
The long-term effects of physical activity （PA） or sedentary behavior on cardiovascular health in young people are not well understood. In this study, we use a narrative format to review the evidence for a prospective association with adiposity and other well-established biological cardiovascular risk factors in healthy young people, considering only studies with at least 2 years of follow-up. PA appears to elicit a long-term beneficial effect on adiposity and particularly markers of cardiovascular health. With adiposity, however, a few studies also reported that higher levels of PA were associated with higher levels of adiposity. Time spent sedentary does not appear to be related to adiposity or markers of cardiovascular health independent of PA. We then discuss the uncertainties in the underlying causal chain and consider a number of alternative modeling strategies, which could improve our understanding of the relationship in future studies. Finally, we consider the current methodology for assessing PA and sedentary time.